Fermentation and Storage Characteristics of “Fuji” Apple Juice Using Lactobacillus acidophilus, Lactobacillus casei and Lactobacillus plantarum: Microbial Growth, Metabolism of Bioactives and in vitro Bioactivities - Yang, Jie; Sun, Yue; Gao, Tengqi; Wu, Yue; Sun, Hao; Zhu, Qingzheng; Liu, Chunsheng; Zhou, Chuang; Han, Yongbin; Tao, Yang (Frontiers in Nutrition, 2022)
Fruit juices have been widely used as the substrates for probiotic delivery in non-dairy products. In this study, three lactic acid bacteria (LAB) strains, including Lactobacillus acidophilus, Lactobacillus casei and Lactobacillus plantarum, were selected to ferment apple juice. During 72-hour of fermentation, these LAB strains grew well in apple juice with significant increases in viable cell counts (from 7.5 log CFU/mL to 8.3 log CFU/mL) and lactic acid content (from 0 to 4.2 g/L), and a reduction of pH value (from 5.5 to around 3.8). In addition, the antioxidant and antibacterial capacities of fermented apple juice were significantly improved through phenolic and organic acid metabolisms. After storage at 4 oC for 30 days, the total amino acid content of fermented apple juice was significantly increased, although the viable cell counts and total phenolic content were decreased (p < 0.05). Furthermore, the fermented apple juice still maintained antibacterial and in vitro antioxidant activities. Overall, all the selected LAB strains could be suitable for apple juice fermentation and can effectively improve their biological activity.